Evaluación del desplazamiento sísmico mediante un análisis no lineal de un edificio de concreto reforzado de sistema combinado y vigas de acople (2020)
An elastic analysis of a structure located in Armenia, Colombia, designed according to the specifications established in the NSR-10, was carry out in order to obtain results with effectiveness. Notwithstanding the above, and considering the existence of different methods to verify the behavior of the structures, which are not mandatory pursuant to NSR-10, a non-lineal analysis was performed according with the ASCE41-17 parameters, in order to corroborate the performance of the building. As a result of the above-mentioned non-lineal analysis, it was obtained that even though the building reached the expected performance objectives, it is necessary to add more shear reinforcement in the structural walls for a correct performance at the structural level of the building.